LRRK2 Kinase Inhibition Rescues Deficits in Lysosome Function Due to Heterozygous GBA1 Expression in Human iPSC-Derived Neurons - Sanyal, Anwesha; Novis, Hailey S.; Gasser, Emile; Lin, Steven; LaVoie, Matthew J. (Frontiers in Neuroscience, 2020)
A growing number of genes associated with Parkinson’s disease are implicated in the regulation of lysosome function, including LRRK2, whose missense mutations are perhaps the most common monogenic cause of this neurodegenerative disease. These mutations are collectively thought to introduce a pathologic increase in LRRK2 kinase activity, which is currently a major target for therapeutic intervention. Heterozygous carriers of many missense mutations in the GBA1 gene have dramatically increased risk of Parkinson’s disease. A critical question has recently emerged regarding the potential interplay between the proteins encoded by these two disease-linked genes. Our group has recently demonstrated that knockin mutation of a Parkinson’s-linked GBA1 variant induces severe lysosomal and cytokine abnormalities in murine astrocytes and that these deficits were normalized via inhibition of wild-type LRRK2 kinase activity in these cells. Another group independently found that LRRK2 inhibition increases glucocerebrosidase activity in wild-type human iPSC-derived neurons, as well as those whose activity is disrupted by GBA1 or LRRK2 mutation. Fundamental questions remain in terms of the lysosomal abnormalities and the effects of LRRK2 kinase inhibition in human neurons deficient in glucocerebrosidase activity. Here, we further elucidate the physiological crosstalk between LRRK2 signaling and glucocerebrosidase activity in human iPSC-derived neurons. Our studies show that the allelic loss of GBA1 manifests broad defects in lysosomal morphology and function. Furthermore, our data show an increase in both the accumulation and secretion of oligomeric -synuclein protein in these GBA1-heterozygous-null neurons, compared to isogenic controls. Consistent with recent findings in murine astrocytes, we observed that multiple indices of lysosomal dysfunction in GBA1-deficient human neurons were normalized by LRRK2 kinase inhibition, while some defects were preserved. Our findings demonstrate a selective but functional intersection between glucocerebrosidase dysfunction and LRRK2 signaling in the cell and may have implications in the pathogenesis and treatment of Parkinson’s disease.